PEMBUATAN ALAT PENGAMAN SEPEDA MOTOR DENGAN MEMANFAATKAN BLUETOOTH BERBASIS ESP 32 - Simanjuntak, Benrad (Universitas Lampung, 2026)
The increasing number of motorized vehicles has led to an increase in crimes against motorcycle users. There are various reasons why motorcycle crimes are committed. One of the main reasons is economic factors. The sale of stolen motorcycles is used to cover daily living expenses because many perpetrators are unemployed. The emergence of new motorcycle products each year is also suspected to be a trigger for criminal acts in the form of motorcycle theft due to the desire to own a vehicle without having to spend money. The lack of motorcycle security during theft conditions makes criminals free to take the victim's motorcycle. In this study, the author created a security system for motorcycles that, in the event of a motorcycle theft, can turn off the engine and sound the horn at a certain distance from the remote and the motorcycle's location using Bluetooth between the remote and the motorcycle.